Biomechanical measures during landing and postural stability predict second anterior cruciate ligament injury after anterior cruciate ligament reconstruction and return to sport - Paterno, Mark V; Schmitt, Laura C; Ford, Kevin R; Rauh, Mitchell J; Myer, Gregory D; Huang, Bin; Hewett, Timothy E (The American journal of sports medicine, 2010)
Athletes who return to sport participation after anterior cruciate ligament reconstruction (ACLR) have a higher risk of a second anterior cruciate ligament injury (either reinjury or contralateral injury) compared with non-anterior cruciate ligament-injured athletes. Prospective measures of neuromuscular control and postural stability after ACLR will predict relative increased risk for a second anterior cruciate ligament injury. Cohort study (prognosis); Level of evidence, 2. Fifty-six athletes underwent a prospective biomechanical screening after ACLR using 3-dimensional motion analysis during a drop vertical jump maneuver and postural stability assessment before return to pivoting and cutting sports. After the initial test session, each subject was followed for 12 months for occurrence of a second anterior cruciate ligament injury. Lower extremity joint kinematics, kinetics, and postural stability were assessed and analyzed. Analysis of variance and logistic regression were used to identify predictors of a second anterior cruciate ligament injury. Thirteen athletes suffered a subsequent second anterior cruciate ligament injury. Transverse plane hip kinetics and frontal plane knee kinematics during landing, sagittal plane knee moments at landing, and deficits in postural stability predicted a second injury in this population (C statistic = 0.94) with excellent sensitivity (0.92) and specificity (0.88). Specific predictive parameters included an increase in total frontal plane (valgus) movement, greater asymmetry in internal knee extensor moment at initial contact, and a deficit in single-leg postural stability of the involved limb, as measured by the Biodex stability system. Hip rotation moment independently predicted second anterior cruciate ligament injury (C = 0.81) with high sensitivity (0.77) and specificity (0.81). Altered neuromuscular control of the hip and knee during a dynamic landing task and postural stability deficits after ACLR are predictors of a second anterior cruciate ligament injury after an athlete is released to return to sport.